2011
DOI: 10.1038/jcbfm.2011.68
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Magnetization Transfer MRI Shows Dysmyelination in an Ischemic Mouse Model of Periventricular Leukomalacia

Abstract: Periventricular leukomalacia, PVL, is the leading cause of cerebral palsy in prematurely born infants, and therefore more effective interventions are required. The objective of this study was to develop an ischemic injury model of PVL in mice and to determine the feasibility of in vivo magnetization transfer (MT) magnetic resonance imaging (MRI) as a potential monitoring tool for the evaluation of disease severity and experimental therapeutics. Neonatal CD-1 mice underwent unilateral carotid artery ligation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 34 publications
(44 reference statements)
5
27
0
Order By: Relevance
“…For quantifying microglia/macrophage activation, we used the proportional area method (Donnelly et al, 2009; Fatemi et al, 2011) to determine the proportion of the ventral or dorsal horn that was Iba1-positive. In addition, we also monitored Iba1-positive cell counts in these regions.…”
Section: Methodsmentioning
confidence: 99%
“…For quantifying microglia/macrophage activation, we used the proportional area method (Donnelly et al, 2009; Fatemi et al, 2011) to determine the proportion of the ventral or dorsal horn that was Iba1-positive. In addition, we also monitored Iba1-positive cell counts in these regions.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a mouse model using unilateral carotid ligation alone (without hypoxia) at P5 has been developed that produces a bilateral white matter injury with some features of PVL (Fatemi et al, 2011). The authors argue that the relative selectivity for white matter is because the insult is milder and inflicted at an earlier age, although the mortality rate from the injury was 25% and, of the animals that survived, almost 10% suffered large hemispheric strokes and had to be excluded from analysis.…”
Section: Modeling White Matter Injury In the Laboratory (Pre-clinicalmentioning
confidence: 99%
“…For quantification of SMI-32 and MBP immunostaining, semiquantitive densitometry was performed using MCID Core (InterFocus Imaging Ltd, Cambridge, UK), as previously published [15]. After calibration with optical density standards, pictures of 5-6 consecutive axial sections were taken covering the area from the first connection of the corpus callosum to its separation.…”
Section: Methodsmentioning
confidence: 99%
“…Histologic studies in ligated animals revealed a bilateral microglial response that correlated with maturational arrest in oligodendrocytes with subsequent myelin pallor and a diffuse axonopathy. Apoptosis measured by caspase 3 staining was almost exclusively limited to OPCs within the white matter tracts [15]. Furthermore, we have also shown immediate up-regulation of proinflammatory cytokines [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation